Estimation method of margin gasdynamic stability of the gas turbine engine while in service - Кінащук, І.Ф.; Кірчу, Ф.І.; Гаоюн, Сунь (Proceedings of National Aviation University (archive), 2005)
Considered is the method of an estimation gasdynamic stability margin of the compressor gas turbine engine under operating conditions. The given way can be used at diagnosing gas turbine engine and gas turbine engine installations.